Hospital bed project for home care - Silva Junior, Aristides José da; Posso, Maria Belén Salazar; Vasconcellos Neto, Laurentino Corrêa de (Revista da Escola de Enfermagem da USP, 2010)
Home care within the health area has largely been improving the life quality of patients and their relatives. It has been an efficient alternative in health care as an answer to meet the needs of patients with chronic diseases, because it does not expose them to nosocomial risks, thus avoiding rehospitalizations and having to stay away from their family life, besides the evident reduction of costs. Nevertheless, it is observed there is a shortage of specific equipments that provide the necessary support in this care modality. The development of a versatile hospital bed that is easily handled is a crucial step for home care. This study addressed the development of a dismountable and lightweight hospital bed that is easy to move, transport and assemble.